Monetary Policy and Automatic Stabilizers: the Role of Progressive Taxation - Fabrizio Mattesini; Lorenza Rossi (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2010)
We study the effects of progressive labor income taxation in an otherwise standard NK model. We show that progressive taxation (i) introduces a trade-off between output and inflation stabilization and affects the slope of the Phillips Curve; (ii) acts as automatic stabilizer changing the responses of the economy to technology shocks and demand shocks (iii) alters the prescription for the optimal discretionary interest rate rule. We also show that the welfare gains from commitment decrease as labor income taxes become more progressive. Quantitatively, the model is able to reproduce the observed negative correlation between the volatility of output, hours and in?ation and the degree of progressivity of labor income taxation.
Keywords: E50; E52; E58; 330